Task-Oriented Processes in Care (TOPIC) Model for Ambulatory Care - John C. Rogers; Jame Corboy; William Huang; F. Marconi Monteiro (Association of American Medical Colleges, 2006)
Abstract This resource is a complete curriculum on the Task-Oriented Processes in Care (TOPIC) model, featuring all of the educational materials developed for use in student and resident teaching on the model, including slides, handouts, videos, case scenarios, and checklists for a TOPIC clinical performance examination. The TOPIC model conceptualizes the work of generalist physicians as processes and tasks during five prototypic visits: new problem visits, checkup visits, chronic illness visits, psychosocial visits, and behavioral change visits. During these visits, clinicians complete four major processes: information processing, patient-physician relationship development, integration of information and relationship, and lifelong learning. Each type of visit includes specific tasks that reflect the purpose of that type of visit. For example, at a chronic illness visit, physicians gather information to assess severity and control of the disease, determine adherence with treatment plan and presence of medication side effects, seek evidence of target-organ damage, and scan for other risk factors for complications. These tasks are different than those for the four other types of visits. Extensive data from performance-based assessments demonstrate that clerkship students and family medicine residents can perform the TOPIC tasks in simulated encounters. Assessment of the curriculum demonstrates that TOPIC is an effective teaching model that spans the continuum of medical education, from students to residents. Since the TOPIC model is a metacognitive framework that focuses on process and not on content or facts, some learners do not immediately appreciate the value of explicitly learning a cognitive strategy for approaching their work. We know that experts use these types of strategies and that novices develop them in the decade it takes to become an expert. TOPIC tries to shorten this developmental period by making the metacognitive thinking explicit, but some learners prefer the more familiar didactic presentations of medical knowledge about specific conditions. This model is robust and can be taught through many educational mediums by a variety of faculty members. The clerkship teaching has been done by different teachers using different seminar processes over the past decade, yet students still learn to perform the tasks in the end-of-clerkship clinical performance examination.